Prognostic Value of Pretreatment Overweight/Obesity and Adipose Tissue Distribution in Resectable Gastric Cancer: A Retrospective Cohort Study - Gu, Lihu; Zhang, Yangfan; Hong, Jiaze; Xu, Binbin; Yang, Liuqiong; Yan, Kun; Zhang, Jingfeng; Chen, Ping; Zheng, Jianjun; Lin, Jie (Frontiers in Oncology, 2021)
Background: This is a study aimed at exploring the relationship between pretreatment overweight/obesity, adipose tissue distribution, and long-term prognosis of gastric cancer. Methods: A total of 607 gastric cancer patients were involved in the retrospective cohort study. Overweight/obese patients were defined as body mass index (BMI) greater than 25 kg/m2 and adipose tissue distribution parameters, including visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), and VAT/SAT ratio were measured at the level of the third lumbar vertebra using computerized tomography images within 15 days before the surgery. Multiple Cox regression models were applied to evaluate the association between overweight/obesity and disease-specific survival (DSS) of gastric cancer and covariates including age, gender, T stage, N stage, and chemotherapy were adjusted. Furthermore, multiple Cox regression models were performed to evaluate the association between adipose tissue distribution parameters and DSS of gastric cancer, except for covariates mentioned above, overweight/obesity was adjusted additionally. Results: Overweight/obesity was a predictive factor (HR = 0.61, 95% CI: 0.37-0.99) for the prognosis of gastric cancer. After additionally adjusting for overweight/obesity, high SAT percentage was an independent protective factor (HR = 0.59, 95% CI: 0.36-0.96), while high VAT percentage (HR = 1.68, 95% CI: 1.06-2.68) and high VAT/SAT ratio (HR = 1.99, 95% CI: 1.19-3.34) were independent risk factors for DSS of gastric cancer. Compared with other patients (overweight/ obesity with low VAT/SAT ratio group, non-overweight/ obesity or high VAT/SAT ratio group), patients in the non-overweight/ obesity with high VAT/SAT ratio group had a worse prognosis (HR = 1.89, 95% CI: 1.28-2.77). Conclusion: These results suggest that overweight/obesity is a predictive factor for the prognosis of gastric cancer. The VAT/SAT ratio could be used as a promising prognostic factor for gastric cancer. Therefore, in preoperative evaluation of gastric cancer patients, attention should be paid not only to BMI but also to adipose tissue distribution.